Economic efficiency of the production of spring wheat fertilized with sulfur against the background of various nitrogen doses - Klikocka-Wiśniewska, Olimpia; Harasim, Elżbieta (Polish Journal of Agronomy, 2022)
The research was carried out on a farm located in Mal- ice (Werbkowice municipality), in the years 2014–2016. The aim of the study was to evaluate the profitability and marginal eco- nomic efficiency of sulfur fertilization of spring wheat at vari- ous levels of nitrogen fertilization. Production value, direct costs and production profitability were assessed, as well as the mar- ginal economic efficiency. On average, the highest grain yield was achieved on the object fertilized with nitrogen at a dose of 150 kg. ha-1 and sulfur in the amount of 40 kg S ha-1. The highest value of direct surplus and, at the same time, the highest profit- ability of production was obtained after nitrogen application in the dose of 100 kg N ha-1. Increasing the nitrogen dose from 50 to 100 kg ha-1 resulted in a significant increase in the grain yield and the achievement of the most favourable marginal economic efficiency index. Among the objects fertilized with nitrogen, the most advantageous in terms of production profitability and mar- ginal economic efficiency was the use of this element in the dose of 100 kg N ha-1. The use of sulfur in the fertilization of spring wheat in the dose of 40 kg S ha-1 slightly improved the fertiliza- tion efficiency in the objects with 50 and 150 kg ha-1. Among the objects fertilized with nitrogen, the most advantageous in terms of production profitability and marginal economic efficiency was the use of this element in the dose of 100 kg N ha-1.